EXPERIMENTAL PRESERVATION OF FISH IN AUREOMYCIN ICE - Velankar, N.P.; Kamasastri, P.V. (Indian Journal of Fisheries, 2015)
Exploratory work carried out in Canada during the last decade on the comparative value of several chemicals and antibiotics in delaying fish spoilage has indicated the possibility of increasing the storage life of iced fish by incorporating trace quantities of antibiotics in the ice (Tarr et al, 1950; Boyd etal, 1953; Gillespie et al, 1955). Among the antibiotics tried so far aureomycin gave most encouraging results, according to the Canadian workers, who employed mainly the bacterial microscopic count for objective evaluation of the quality of fish in storage. These workers reported aureomycin to be effective at levels of 1 to 2 p.p.m. Velankar (1957) who examined the effect of aureomycin on the growth of a number of bacterial species isolated from marine sources, i.e., sea-water, marine mud, plankton, fresh and spoiling sea-fish, found that at the level of 2 p.p.m. aureomycin delayed growth in 40%, while at the level of 5 p.p.m. growth was delayed in the case of 70%, of the bacteria. Work reported from the Torry Research Station, Aberdeen, based on bacteriological, chemical and organoleptic examination of the fish also indicates that a concentration of 5 p.p.m. of aureomycin in the ice is necessary for increasing the storage life significantly (Ingram et al., 1956). The use of different species of fish, and also different criteria for assessing the state of preservation of the fish in storage, in the investigations of the Canadian and British workers probably explain the different findings.